Analytical and numerical methods for vibration analyses - Wu, Jong-Shyong. (Hoboken, NJ : John Wiley & Sons Inc., 2013)
"This book illustrates theories and associated mathematical expressions with numerical examples using various methods, leading to exact solutions, more accurate results, and more computationally efficient techniques. It presents the derivations of the equations of motion for all structure foundations using either the continuous model or the discrete model. It discusses applications for students taking courses including vibration mechanics, dynamics of structures, and finite element analyses of structures, the transfer matrix method, and Jacobi method"--
"A book to introduce the theories or methods presented in some of the author's publications appearing in the international journals"--
5.6 Solution of Semi-Definite System with Generalized Jacobi Method5.7 Solution of Damped Eigenproblem; References; Chapter 6: Vibration Analysis by Finite Element Method; 6.1 Equation of Motion and Property Matrices; 6.2 Longitudinal (Axial) Vibration of a Rod; 6.4 Flexural Vibration of an Euler-Bernoulli Beam; 6.5 Shape Functions for a Three-Dimensional Timoshenko Beam Element; 6.6 Property Matrices of a Three-Dimensional Timoshenko Beam Element; 6.7 Transformation Matrix for a Two-Dimensional Beam Element; 6.8 Transformations of Element Stiffness Matrix and Mass Matrix
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Vibration -- Mathematical models; Structural analysis (Engineering) -- Mathematical models; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Structural analysis (Engineering) -- Mathematical models; Vibration -- Mathematical models; Electronic books